A state-of-the-art review on potential applications of natural fiber-reinforced polymer composite filled with inorganic nanoparticle - Mishra, Trilokinath; Mandal, Paulami; Rout, Arun Kumar; Sahoo, Dibakar (Composites. Part C, Open access, 2022)
Natural fibres have recently piqued the interest of researchers due to their low cost, availability, sustainability, renewable, and biodegradable properties, which can also be used as reinforcement in polymer composites. Numerous researches are going on to improve the mechanical and tribological properties of these engineered biocomposites with the filling of the appropriate amount of inorganic nanoparticles like ZrO2, SiO2, CuS, ZnO, CuO, and TiO2 into polymer matrices. The composites were made with different weight fractions of nanoparticles using various moulding techniques, such as hand lay-up, vacuum-assisted resin transfer moulding, pultrusion, injection moulding, and so on. Before fabrication, the natural fibers undergo different chemical treatments, such as alkaline, silane, acetylation, or benzoylation, etc. Mechanical tests (tensile, compression, flexural, hardness, and impact), tribological tests (coefficient of friction and wear rate), and water absorption tests were commonly performed. The purpose of this review is to discuss the mechanical, falme retardant, thermal, tribological, water adsorption, and biodegradable properties of the inorganic nanoparticle-filled natural reinforced polymer composite and their applications. Our review reveals that the incorporation of inorganic nanoparticles into a natural fiber reinforced polymer composite improved mechanical and tribological properties, it is also enhanced thermal stability and flame retardancy and reduced the water absorption capacity of biocomposites. Inorganic nanoparticle-filled natural reinforced polymer composite has higher degradability and causes less environmental pollution and these biocomposites show their utility in construction, packaging, furniture, automotive industries, and biotechnological fields. [Display omitted]